Da[má]ternagem e suas pulsões: a crueldade na função materna sob o olhar psicanalítico. - Melo, Guaíra Moreira Camilo de (2017)
This research emerged from the interest in understanding the cases, increasingly propagated in media vehicles, of infants killed or severely abused by people to whom are commonly atributed expressions of love and care as mothers, stepmothers and grandmothers. Such events foster inquiries about this social symptom, especially about the psycho-affective history of these females perpetrators of cruelty, because they are against the supposed innate tendency toward maternal love that is presupposed to the feminine. From the theoretical contributions of Sigmund Freud, Sándor Ferenczi, Elizabeth Badinter and Françoise Couchard, we reflect on what developments these cases can bring to psychoanalytic clinic and criminology today. In order to investigate the manifestations of cruelty perpetrated by women against children under their care, we propose to think what leads, from the point of view of psychoanalytic theory, a woman to take responsibility under a child to commit cruel acts; to understand how the maternal function is expressed in these women and to analyze what in the history of the psycho-affective development of these women may be repeating itself towards the possible identification to a previous aggressor. To do so, we chose documentary research to study the trial data of two cases of women accused of torturing children they took under their care. It was identified in these processes aspects that pointed to the creation of a psychoaffective history of these women, where it was possible to conjecture that the broken and ill family bond that probably contributed to the abuses suffered by the women during their childhood possibly provided an identification of them with their aggressors and the consequent repetition of their acts, which, established in a relationship of domination, enabled them to live an active life of this cruelty drive.